An Identification Method of Metering Anomaly Based on Line Loss Analysis of Low Voltage Station. Issue 1 (1st December 2022) - Qin, Yuewei; Cui, He; Zhang, Muxin
Abstract: Abnormal measurement on the power side is an important reason for abnormal statistical line loss. Considering that there are many abnormal measurement reasons, it is very difficult to rely on on-site investigation alone. To overcome this problem, a method based on line loss analysis in low voltage stations is proposed. In order to ensure the true and reliable analysis results, this paper combines the management standard of the line loss of the low-voltage platform area and the actual operation situation of the platform area, analyzes the measurement factors affecting the line loss of the low-voltage platform area, and extracts the analysis rules and calculation model of the abnormal measurement factors. In order to improve the efficiency of on-site investigation, this paper combines data analysis and proposes abnormal identification method with fault prediction. This method can analyze the possible abnormal causes before on-site investigation and improve the accuracy of on-site line loss verification. Finally, the accuracy and effectiveness of the calculation anomaly analysis model and the identification method are verified.